Necrotizing pneumonia among Italian children in the pneumococcal conjugate vaccine era. Issue 5 (1st February 2021) - Carloni, Ines; Ricci, Silvia; Rubino, Chiara; Cobellis, Giovanni; Rinaldelli, Giampaolo; Azzari, Chiara; de Benedictis, Fernando M.
Abstract: Background: Necrotizing pneumonia (NP) is a severe complication of community‐acquired pneumonia. The impact of 13‐valent pneumococcal conjugate vaccine (PCV13) on the epidemiology of NP in children has not been assessed. Patients and methods: Medical records of children less than 18 years admitted with NP to two pediatric hospitals in Italy between 2005 and 2019 were reviewed. The following four periods were defined: 2005–2010 (pre‐PCV13), 2011–2013 (early post‐PCV13), 2014–2016 (intermediate post‐PCV13), and 2017–2019 (late post‐PCV13). Results: Forty‐three children (median age, 44 months) were included. Most of them (93%) were previously healthy. No differences in age, sex, season of admission, comorbidity, clinical presentation, or hospital course were identified between pre‐PCV13 and post‐PCV13 periods. A significant decrease in the rate of NP‐associated hospitalizations was found between the early (1.5/1000 admissions/year) and the intermediate (0.35/1000 admissions/year) post‐PCV13 period ( p  = .001). An increased trend in admissions was found thereafter. Streptococcus pneumoniae was the most common agent detected in both periods (pre‐PCV13: 11/18, 61%; post‐PCV13: 13/25, 52%). Serotype 3 was the most common strain in both periods (pre‐PCV13: 3/11, 27%; post‐PCV13; 4/13, 31%). There were no changes in the etiology over time, but most patients with Streptococcus pyogenes or Staphylococcus aureus infection were admitted during the post‐PCV13 period. Conclusions: The hospitalization rate for NP in children decreased a few years after the implementation of PCV13 immunization in Italy. However, an increased trend in admissions was found thereafter. S. pneumoniae was the most frequent causal agent in both pre‐ and post‐PCV13 periods. Pneumococcal serotypes were mainly represented by Strain 3.